Anterior visual pathway cavernous malformations. Issue 2 (February 2015) - Tan, Terence; Tee, Jin W.; Trost, Nicholas; McKelvie, Penny; Wang, Yi Yuen
Abstract Anterior visual pathway cavernous malformations (CM) are rare diagnoses with poorly-defined natural history and management. A systematic review of all reports of anterior visual pathway CM was performed to identify all English-language articles with histopathologically-proven anterior visual pathway CM published from 1950 to December 2013. Patient demographics, presenting symptoms, CM location, treatment modality and clinical outcome were recorded and analyzed. The case of a 60-year-old woman from our institution with acute-on-chronic visual disturbance secondary to visual pathway CM is presented. Including the current patient, 70 cases of anterior visual pathway CM have been published to our knowledge. The average patient age is 34.8 ± standard deviation of 14.2 years, with a female preponderance (n = 37, 52.9%). The majority of patients had an acute (n = 44; 62.9%; 95% confidence interval [CI] 0.51–0.73) onset of symptoms. In at least 55.6% (n = 40) of patients, the cause of visual disturbance was initially misdiagnosed. The majority (91.4%; n = 64) of patients underwent craniotomy, with complete resection and subtotal resection achieved in 53.1% (n = 34; 95%CI 0.41–0.65) and 17.2% (n = 11; 95%CI 0.10–0.28) of all surgical patients, respectively. Comparing surgically managed patients, complete resection improved visual deficits in 59.0% (n = 20; 95%CI 0.42–0.75), while subtotal resection improved visual deficits in 50.0% (n = 5; 95%CI 0.24–0.76; p = 0.62). CM is an important differential diagnosis for suprasellar lesions presenting with visual disturbance. A high index of suspicion is required in its diagnosis. Expeditious operative management is recommended to improve clinical outcomes.